2010
DOI: 10.1111/j.1365-2311.2009.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of ecological generalism with special reference to conservation biological control

Abstract: Abstract. 1. If ecological generalism is an evolving heritable trait, we need to study the underlying genetics in order to understand the nature of this fundamental phenomenon.2. I consider two alternatives. Under the Type I mechanism, ecological generalism is exclusively a population property. Under the Type II mechanism, generalism can vary among genotypes as well as among populations.3. The genetics underlying the Type I mechanism is straightforward, whereas Type II genetics is less so. I propose that a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…He showed that the pattern of relationship depended on the geographical scale such as continent and local area, and suggested that the diet breadth of each butterfly species varies, even within a local area, and the determination of diet breadth of species can be regionally different. The level of generalism in diverse insect groups varied according to the species' geographic range (Emelianov ). The present study referred to the diet breadth of Japanese butterflies, so errors from the regional variation of the diet breadth were not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…He showed that the pattern of relationship depended on the geographical scale such as continent and local area, and suggested that the diet breadth of each butterfly species varies, even within a local area, and the determination of diet breadth of species can be regionally different. The level of generalism in diverse insect groups varied according to the species' geographic range (Emelianov ). The present study referred to the diet breadth of Japanese butterflies, so errors from the regional variation of the diet breadth were not excluded.…”
Section: Discussionmentioning
confidence: 99%